Incidence of Congenital Hypothyroidism in the Newborn of A Tertiary Hospital in Southern Bangladesh - Rasul, CH; Lucky, SN; Miah, SR; Moslem, F (Bangladesh Journal of Child Health, 2010)
Background: Congenital hypothyroidism is the commonest preventable cause of mental retardation. It is more prevalent in endemic goiter regions like Bangladesh. But magnitude of the problem has not been studied at national level. Objective: To detect the incidence of congenital hypothyroidism among the newborn delivered in Khulna Medical College Hospital in southern part of Bangladesh and to rationalize the development of neonatal screening program. Methodology: All the living newborns delivered between Oct '01 to June ‘05 in Khulna Medical College Hospital were included in the study. After taking the relevant information from mother, cord blood sample were collected from the newborn within 24 hours of birth and kept in freezer. At the end of collection of each two month, the lot of blood sample was sent to the laboratory of Institute of Nuclear Medicine, Dhaka for radioimmunoassay of TSH. Potential cases with TSH value above 10 MIU/L were recalled for thyroid function test for confirmation of diagnosis. Results: After discarding unsatisfactory samples, 1353 samples were assayed for TSH. Among the study population 88.2% hailed from Khulna district and the rest of the cases came from neighboring districts. Male to female ratio was 1.2:1. Regarding the birth weight 33.4% babies were of low birth weight. TSH above 10 MIU/L were found in 35 babies among whom one baby was hypothyroid and the other member of the twin was also hypothyroid although the TSH level was below 10 MIU/L. Thus incidence of congenital hypothyroidism was 1.5 per thousand living newborn among the studied cases. Conclusion: The incidence of congenital hypothyroidism in southern part of the country is quite high in relation to global incidence. Although this is not the national picture but the high figure is alarming. So, neonatal screening program should be implemented as soon as possible to find out the real case burden in the community and thereby to take care of them and reduce the number of mentally retarded children in our country. Key words: Congenital hypothyroidism; neonatal screening; mental retardation. DOI: 10.3329/bjch.v29i3.6186 Bangladesh J Child Health 2005; Vol 29 (3): 88-92